Inspección, evaluación y priorización de 8 puentes utilizando el Proceso Analítico Jerárquico - Salazar-Guzmán, Tatiana (Instituto Tecnológico de Costa Rica, 2012)
The bridges are built to communicate two places between which there is a river, canal or other obstacle that impede communication. Land transportation is the most used in Costa Rica, so the state of bridges and roads should to be optimal to allow a perfect national development in economic, technological and social. This work discloses the evaluation methodology contained in the Guidelines Manual for Bridge Maintenance, this is used to determine the degree of deficiency and priority repair eight bridges located on the stretch between Liberia and Cañas on the route nacional1. Are evaluated two types of bridges: truss and beam, because they are those that can be evaluated with the manual. This study discloses a better retention in the steel girder bridges and truss. After, predominant damage on the pavement and expansion joints. The correct management of bridges in Costa Rica is complicated by the lack of planning, lack of trained personnel, equipment and basic tools. Therefore, improvements are proposed, and a comparison is made with the systems of other countries.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2012.
Keywords: Inventario; Superestructura; Puente; Administración; Daño